2012
DOI: 10.1371/journal.pntd.0001761
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Enhance Susceptibility to Experimental Trypanosoma Congolense Infection Independent of Mouse Genetic Background

Abstract: BackgroundBALB/c mice are highly susceptible while C57BL/6 are relatively resistant to experimental Trypanosoma congolense infection. Although regulatory T cells (Tregs) have been shown to regulate the pathogenesis of experimental T. congolense infection, their exact role remains controversial. We wished to determine whether Tregs contribute to distinct phenotypic outcomes in BALB/c and C57BL/6 mice and if so how they operate with respect to control of parasitemia and production of disease-exacerbating proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In addition, infected mice also show a reduced antibody response to sheep red blood cells (SRBC) following immunization (44)(45)(46)(47)(48). Several mechanisms have been proposed as the cause of trypanosomeinduced immunosuppression, including macrophages (49), suppressor T cells (50), nitric oxide (NO) (51), and Tregs (24,25). Recent reports (including those from our laboratory) have shown that conventional and naturally occurring Tregs (characterized as CD4 ϩ CD25 ϩ Foxp3 ϩ ) contribute to enhanced susceptibility to experimental T. congolense infection in mice (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, infected mice also show a reduced antibody response to sheep red blood cells (SRBC) following immunization (44)(45)(46)(47)(48). Several mechanisms have been proposed as the cause of trypanosomeinduced immunosuppression, including macrophages (49), suppressor T cells (50), nitric oxide (NO) (51), and Tregs (24,25). Recent reports (including those from our laboratory) have shown that conventional and naturally occurring Tregs (characterized as CD4 ϩ CD25 ϩ Foxp3 ϩ ) contribute to enhanced susceptibility to experimental T. congolense infection in mice (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In experiments requiring Treg depletion, each mouse received 100 g of anti-CD25 monoclonal antibody (MAb) (clone PC61) intraperitoneally. Previous studies from our lab have shown that this dose of antibody causes sustained depletion of CD25 ϩ Foxp3 ϩ T cells (without affecting other cell populations) for up to 7 days in mice infected with T. congolense (25,30). In vivo depletion of macrophages was done by intravenous injection of 200 l of chlodronateloaded liposomes (5 mg/ml; Encapsular NanoSciences LLC, Nashville, TN) 24 h before primary intradermal infection.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations